Comparison of clinical outcomes following early rehabilitation in 3 cases of nephrotic syndrome with different treatment courses - Iwai, Kohji; Hatanaka, Yasuhiko; kawaguchi, Tamiro; Araki, Shin-ich (CEN case reports, 2020)
There have been few published reports regarding rehabilitation for nephrotic syndrome. We compared the clinical outcomes of three cases of nephrotic syndrome with different treatment courses during 5 weeks of early rehabilitation. We report on three cases of nephrotic syndrome. Case 1 was a 67-year-old male who showed good progress after steroid treatment. Quadriceps torque and exercise capacity were increased after intervention. Case 2, a 78-year-old male, demonstrated resistance to steroid treatment. Quadriceps torque was decreased and exercise capacity was increased after intervention. Case 3 was an 83-year-old male who received nutrition therapy and diuretics without steroid treatment. Quadriceps torque and exercise capacity were decreased post-intervention. Early rehabilitation should be considered even if the steroid treatment course is different; furthermore, it is necessary to carefully consider the optimal exercise load in patients with nephrotic syndrome for whom regardless of whether or not steroid treatment is used.